Beyond Andragogy: New Directions in Adult Learning Theory - Sharan B. Merriam (Adult Education Research Conference, 2009)
While andragogy is here to stay, we have moved beyond centering it at the heart of adult learning theory. Five other ways to understand adult learning will be presented in this symposium: transformative learning, spirituality and adult learning, embodied knowing, the neuroscience of adult learning and narrative learning.